2023
DOI: 10.1002/brb3.3068
|View full text |Cite
|
Sign up to set email alerts
|

Gestational age‐related changes in relaxation times of neonatal brain by quantitative synthetic magnetic resonance imaging

Abstract: Objective: This study aimed to explore the correlation between T1 and T2 relaxation times of synthetic MRI (SyMRI) and gestational age (GA) in each hemisphere of preterm and term newborns at the initial 28 days of birth. Methods: Seventy preterm and full-term infants were prospectively included in this study. All subjects completed 3.0 T routine MRI and SyMRI (MAGiC) one-stop scanning within 28 days of birth (aged 34-42 W at examination). The SyMRI postprocessing software (v8.0.4) was used to measure the T1 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 57 publications
0
0
0
Order By: Relevance
“…Vanderhasselt et al reported that neonates with severe postnatal disorders had prolonged local tissue relaxation times, particularly in the PLIC and the central portion of the CS, which had the highest accuracy in predicting at-risk status [ 20 ]. Recent studies have shown that the T1 and T2 relaxation values obtained by SyMRI are closely related to the degree of myelin development, which can reflect subtle differences in early brain development and is an effective indicator for assessing brain maturity [ 8 ]. In this study, we quantitatively assessed the preoperative brain development of infants and children with CHD by SyMRI, compared the differences in relaxation values between the two groups of subjects in different brain regions, and analyzed the correlation between the significantly different parameter values and Gesell development scores.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vanderhasselt et al reported that neonates with severe postnatal disorders had prolonged local tissue relaxation times, particularly in the PLIC and the central portion of the CS, which had the highest accuracy in predicting at-risk status [ 20 ]. Recent studies have shown that the T1 and T2 relaxation values obtained by SyMRI are closely related to the degree of myelin development, which can reflect subtle differences in early brain development and is an effective indicator for assessing brain maturity [ 8 ]. In this study, we quantitatively assessed the preoperative brain development of infants and children with CHD by SyMRI, compared the differences in relaxation values between the two groups of subjects in different brain regions, and analyzed the correlation between the significantly different parameter values and Gesell development scores.…”
Section: Discussionmentioning
confidence: 99%
“…Synthetic magnetic resonance imaging (SyMRI) is an emerging imaging modality that facilitates quantitative analysis of tissues by simultaneously obtaining multiple contrast images and multiple quantitative maps in a single scan over a short period. Studies on quantitative relaxation values in the central nervous system have been reported in the literature [ 6 8 ]. Quantitative information, such as longitudinal relaxation time (T1) and transverse relaxation time (T2) relaxation values, which can reflect changes in the myelin content of the brain, can aid imaging physicians in the detection of subtle brain lesions.…”
Section: Introductionmentioning
confidence: 99%